Cryotherapy versus fractional carbon dioxide laser in patchy alopecia areata: a self-controlled comparative study - Ahmed A. Afify; Maha A. Shaheen; Mays Q. Ojaimi (Journal of the Egyptian Women’s Dermatologic Society)
Introduction Alopecia areata (AA) is an autoimmune noncicatricial alopecia. Many treatments are available but with variable results. Few studies have reported fractional carbon dioxide (FCO2) laser and cryotherapy in treating AA through various mechanisms. Objective This study aimed to assess the efficacy and safety of FCO2 laser in comparison to cryotherapy in the treatment of AA. Patients and methods This prospective self-controlled comparative study included 22 patients with patchy AA (3 patches). The three patches in each patient were treated by one of the following methods by simple randomization: FCO2 laser, cryotherapy, and the third patch was left without treatment as a control. The sessions were repeated every 2 weeks for six sessions. Results Comparison of single-blinded dermatologist assessment of clinical response between the three groups revealed a statistically significantly better response with FCO2 laser and cryotherapy compared with control patches, but there was no statistically significant difference between the FCO2 laser group versus the cryotherapy group (P=1). Comparison between trichoscopic hair parameters before and after treatment showed a significant decrease in black dots, yellow dots, and exclamation mark hair count in both cryotherapy and FCO2 groups. Short vellus hair count showed a significant increase after treatment in the FCO2 group. Exclamation mark hair count before treatment was significantly higher than after treatment in the control group. Conclusion Both cryotherapy and FCO2 laser therapy are effective and safe in patchy AA treatment with nearly similar efficacy.